Chiller energy consumption prediction : methods and system development - Xiao, Qianru (2016)
Power consumption is critical in organization operations, for various reasons including financial saving and environment protection. Power usage prediction helps organization to understand how energy consumption is affected by different factors, and therefore provides decision-making support for further energy optimization. Many organizations use historical consumption pattern to estimate future trend, which lacks accuracy and credibility. Internet of Things and data analytics offer solutions to address this problem by collecting and modelling large amount of data.